Identifikasi Iris Mata Menggunakan Alihragam Wavelet Haar - Prihartono, Teguh Dwi; Isnanto, R. Rizal; Santoso, Imam (Transmisi, 2011)
Human iris has a very unique pattern which is different for each person so it is possible to use it as a basic of biometric recognition. To identify texture in an image, texture analysis method can be used. There is some texture analysis method,one of them is wavelet that extract the feature of image based on energy. The texture analysis using energy features which are in the wavelet transform. Based on that reason, in this research made a simulation to identified eyes iris based on Haar wavelet transform. First, the image of iris is segmented from eye image then enhanced with histogram equalization. The method used to extract the feature is Haar wavelet transform. The features obtained is energy value. The next step is recognition using normalized Euclidean distance. Four experiments are done in the research, those are influence of number of sample in database, influence of Haar wavelet transform level, influence of different input image format and testing on eye images which are not in database. As the result, the highest accuration is achieved using Haar wavelet transform level 4 with two samples iris image saved is 85,58%. The lowest accuration is achieved using Haar wavelet transform level 1 with one sample iris image saved is 65,27%. Then, from the test result for the influence of different input image format, the .bmp input image format is better than .jpg input image format. Whereas, from the test result for eye images which are not in database with threshold 2,3653, the recognition level is 81,48%. Keyword : biometric, human iris, texture analysis, Haar wavelet transform, Euclidean distance